Validation of agonist and antagonist muscle force estimation during jumping at three different effort levels - Ford, K. R.; van den Bogert, A. J.; Myer, G. D.; Shapiro, R.; Hewett, T. E. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Non-invasive analyses of neuromuscular control and joint loading are critical to the delineation of the potential mechanisms that underlie increased risk of musculoskeletal injury. Static optimization techniques may be used in an attempt to resolve the indeterminacy of muscle forces. While debate remains concerning the ability to correctly estimate forces in antagonistic muscles, methods are technically feasible and should be validated to determine if they provide physiologically accurate data (Herzog and Binding 1992). The purpose of this project was to validate a static optimization musculoskeletal model used to estimate lower extremity muscle forces. Specifically, EMG patterns of agonist/antagonist muscles were compared to estimated muscle forces during counter-movement jumps at varied efforts.